FAKTOR-FAKTOR YANG MEMPENGARUHI EARNINGS RESPONSE COEFFICIENT (ERC) - Subagyo .; Cicilia Novita Olivia (Universitas Kristen Krida Wacana, 2012)
Publication of financial statements through the mass media can influence an investment decision prospective investors. This is due to the information contained in financial statements is considered the latest news about the state of the company in the capital market. Reflection of the ERC depends on the